2023
DOI: 10.3390/toxins15020132
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Transport Mechanism of Red Meat-Derived N-glycolylneuraminic Acid and Its Damage to Intestinal Barrier Function through the NF-κB Signaling Pathway

Abstract: N-glycolylneuraminic acid (Neu5Gc) is a specific factor in red meat that induces intestinal disease. Our aim was to investigate the effect of Neu5Gc on the intestinal barrier as well as its mechanism of endocytosis and exocytosis. Ten specific inhibitors were used to explore the mechanism of Neu5Gc endocytosis and exocytosis by Caco-2 cells. Amiloride hydrochloride and cytochalasin D had the strongest inhibitory effect on the endocytosis of Neu5Gc. Sodium azide, dynasore, chlorpromazine hydrochloride, and nyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A recent study on cells demonstrated that Neu5Gc activates NF‐κB signaling pathway, triggers the release of pro‐inflammatory factors, and disrupts intestinal barrier function (He et al., 2023). In the context of xenotransplantation, the presence of Neu5Gc, which is accumulated through human diet, combined with anti‐Neu5Gc antibodies, can lead to transplant rejection, increase its immunogenicity, and decrease the success rate of transplantation (Paul & Padler‐Karavani, 2018).…”
Section: Neu5gcmentioning
confidence: 99%
“…A recent study on cells demonstrated that Neu5Gc activates NF‐κB signaling pathway, triggers the release of pro‐inflammatory factors, and disrupts intestinal barrier function (He et al., 2023). In the context of xenotransplantation, the presence of Neu5Gc, which is accumulated through human diet, combined with anti‐Neu5Gc antibodies, can lead to transplant rejection, increase its immunogenicity, and decrease the success rate of transplantation (Paul & Padler‐Karavani, 2018).…”
Section: Neu5gcmentioning
confidence: 99%